Validitas Modul Berbasis Website pada Materi Ekosistem untuk SMA Kelas X - Zikra Zikra; Dwi Resti Avriananda; Evrialiani Rosba (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Limited teaching materials used by teachers and students such as printed books make it difficult for teachers to provide explanations and students find it difficult to understand learning outside of school. The textbooks used in general are good but need to be updated because the pictures presented in the printed books are not clear and are in black and white. Teachers rarely use modules and teachers never use web-based teaching materials. With internet facilities that are already available, teachers can further improve the quality of learning activities, such as using web-based teaching materials as learning resources. Therefore, by utilizing the internet as a learning resource, simple teaching materials are needed, namely website-based modules. This study validates a web-based module on ecosystem material for class X SMA. website based. The method used in this research is development (Research & Development) with the ADDIE model. The stages of development research are carried out with several stages that have been modified according to the needs of researchers, namely: 1) the analysis stage; 2) the design stage (design); and 3) development stage. At the analysis stage, needs analysis is carried out, at the design stage, modules are compiled, and at the development stage, expert validation is carried out. The instrument used in this study is a validation sheet which includes validation of the feasibility of content, language, presentation, graphics, and media use. The results showed that the validity of the website-based module was very valid with an average of 91%. Based on these results it can be concluded that the resulting website-based module is very valid and suitable for use as teaching material.